Fe-Catalyzed insertion of fluoromethylcarbenes generated from sulfonium salts into X–H bonds (X = Si, C, P). Issue 10 (27th June 2017) - Duan, Yaya; Lin, Jin-Hong; Xiao, Ji-Chang; Gu, Yu-Cheng
Abstract : The Fe-catalyzed insertion of fluoromethylcarbenes including trifluoromethylcarbene and difluoromethylcarbene into X–H (X = Si, C and P) bonds is described. Abstract : The Fe-catalyzed insertion of fluoromethylcarbenes including trifluoromethylcarbene and difluoromethylcarbene generated in situ from sulfonium salts (Ph2 S + CH2 CF3 − OTf and Ph2 S + CH2 CF2 H − OTf) into X–H (X = Si, C and P) bonds is described. The insertion of both carbenes into the Si–H bond occurred smoothly, and trifluoromethylcarbene could also insert into C–H and P–H bonds.